(untitled) (CIPEEX, 2026)
This paper presents the "State of the Art" written as a scientific basis for the development of a Master’s Dissertation, currently being developed in the Stricto Sensu Graduate Program in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda includes the importance of green social reintegration as an alternative method for serving sentences in semi-open prisons, a form of restorative justice to be implemented in the districts of the state of Goiás that do not have agricultural colonies. To achieve this, a deductive approach was employed, enhanced by bibliographic and documentary techniques, which allowed for the development of descriptive and explanatory research.